Digital hypertension management: clinical and cost outcomes of a pilot implementation of the OMRON hypertension management platform - Holmstrand, Ericka C.; Sato, Hironori; Li, Jim; Mukherjee, Abhishek; Fitzpatrick, Nicole E.; Rayl, Kenneth R.; Colangelo, Francis R. (Frontiers in Digital Health, 2023)
Question: Can use of the OMRON Hypertension Management Platform decrease utilization and cost of hypertension-related healthcare services? Findings: In this quality improvement (QI) project of 187 adults with primary hypertension, both the number and cost of hypertension-related claims were significantly increased in the six months following enrollment, compared to propensity score-matched controls.Meaning: Use of a digital platform to improve home monitoring of blood pressure may increase healthcare utilization in the short-term.